Repetitive Peripheral Magnetic Stimulation (rPMS) in Subjects With Lumbar Radiculopathy: An Electromyography-guided Prospective, Randomized Study - SAVULESCU, SIMONA ELENA; BERTEANU, MIHAI; FILIPESCU, IULIA; BEIU, CRISTINA; MIHAI, MARA-MADALINA; POPA, LILIANA GABRIELA; POPESCU, STELLA IOANA; BALESCU, IRINA; BACALBASA, NICOLAE; POPESCU, MARIUS-NICOLAE (In vivo (Athens), 2021)
Lumbar radiculopathy refers to the disruption of one or more lumbosacral nerve root functions, usually causing radiating pain and functional impairments. We aimed to analyze the role of repetitive peripheral magnetic stimulation (rPMS) alone or in association with physiokinesiotherapy (PKT) in treating lumbar radiculopathy. A total of 41 patients diagnosed with lumbar radiculopathy were randomly allocated to the rPMS group and the rPMS plus PKT group. Subjects were then administered a total of 10 treatment sessions. A statistically significant improvement was highlighted in both groups in terms of pain score, and electromyography (EMG) analysis depicted a far superior functional recovery in the rPMS plus PKT group. rPMS can constitute an effective treatment for subjects with lumbar radiculopathy and its association with a complex physical rehabilitation program could improve the outcome in these patients.